Efficacy of pragmatic same-day ring prophylaxis for adult individuals exposed to SARS-CoV-2 in Switzerland (COPEP): protocol of an open-label cluster randomised trial. Issue 11 (12th November 2020) - Smit, Mikaela; Marinosci, Annalisa; Nicoletti, Giovanni Jacopo; Perneger, Thomas; Ragozzino, Silvio; Andrey, Diego O; Stoeckle, Marcel; Jacquerioz, Frederique; Lebowitz, Dan; Agoritsas, Thomas; Meyer, Benjamin; Spechbach, Herve; et al.
Abstract : Introduction: Lopinavir/ritonavir (LPV/r) has been proposed as repurposed drugs for pre-exposure and postexposure prophylaxis as well as therapy of COVID-19. Coronavirus postexposure prophylaxis (COPEP) trial aims at assessing their efficacy as postexposure ring-prophylaxis among adults exposed to SARS-CoV-2. Methods and analysis: COPEP is a two-arm open-label cluster-randomised trial conducted in three cantons of Switzerland. Asymptomatic contacts (≥16 years) of individuals diagnosed with COVID-19 will be randomised (2:1) to either LPV/r (400 mg/100 mg two times per day) for 5 days, or a standard of care arm (no treatment). Asymptomatic individuals may be either SARS-CoV-2 positive or negative. Contacts living in the single household will form a cluster and will be randomised into the same arm. All participants will be followed-up for 21 days and undergo daily monitoring for COVID-19 symptoms. The primary endpoint is 21-day incidence of laboratory-confirmed COVID-19 with ≥1 compatible symptom, analysed in an intention-to-treat (ITT) analysis. The secondary endpoints include the 21-day incidence of COVID-19 as well as SARS-CoV-2 infection in a modified ITT analysis, excluding participants who had a positive SARS-CoV-2 RT-PCR from oropharyngeal swab and/or a positive SARS-CoV-2 IgG serology at baseline. Assuming a 21-day incidence for COVID-19 of 20% among contacts without postexposure chemoprophylaxis, to detect a relative risk reduction of 60% (ie, translating in an absolute reduction from 20% to 8%), with a power of 80%, an alpha of 5%. Accounting for design effect of cluster design of circa 1.1, we plan to enrol 200 participants to the LPV/r arm and 100 to the standard of care arm, 300 participants in total. Ethics and dissemination: Ethics approval has been granted by the Commission Cantonale d'Ethique de la Recherche, Ethikkommission Nordwest- und Zentralschweiz and Comitato Etico Cantonale (ref 2020-00864) and Swissmedic (2020DR3056). Results from this trial will be disseminated via journal articles and presentations at national and international conferences. Trial registration number: Clinicaltrials.gov Registry (NCT04364022 ); Swiss National Clinical Trial Portal Registry (SNCTP 000003732). Registered report identifier: CCER 2020-0864.